ØªØÙ„ÙŠÙ„ ÙƒØªØ§Ø¨ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© ØªÙ…Ø¨Ø§ÙƒØ¨Ø±Ø§Ø³ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ Ù…Ù† ÙˆØ¬Ù‡Ø© Ø§Ù„Ù†Ø¸Ø± Ø¹Ù„Ù‰ Ù…Ø§ÙƒÙŠ - Mujib, Ahmad; Masykur Afandi, Muh. (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2020)
The purpose of this study are to select the material, the gradations in the textbook, material presentation and material repetition in this book is presented well. The research method used is descriptive qualitative approach with macky theory and the type of researcher in the form of library research. While data analysis used analysis content according to Kilizirmak. The result of the study include: 1) the selection of material in Arabic textbooks MAN Tambakberas Jombang by Muhammad Ilyas has fulfilled the criteria. But in terms of material content there is no scope for sound, and in terms of meaning, no rhetoric is found, and other language fields, 2) gradations in the textbook are classified as simple with complicated material to the students' needs, 3) material presentation in this book it is well presented and with pictures that support, 4) the last material repetition in this book is well presented, but it needs to be included in a field where it is incomplete such as the flashing of views, stories, slogans, singing, etc.